2020
DOI: 10.5194/acp-2020-135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurements of carbonyl compounds around the Arabian Peninsula indicate large missing sources of acetaldehyde

Abstract: Abstract. Volatile organic compounds (VOCs) were measured around the Arabian Peninsula using a research vessel during the AQABA campaign (Air Quality and Climate Change in the Arabian Basin) from June to August 2017. In this study we examine carbonyl compounds (CxHyO), measured by a proton transfer reaction mass spectrometer (PTR-ToF-MS), and present both a regional concentration distribution and a budget assessment for these key atmospheric species. Among the aliphatic carbonyls, acetone had the highest mixin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…This study focuses on the two crossings of the Arabian Sea during the AQABA campaign. The Arabian Sea was generally characterized by low values of VOCs, especially VOCs related to anthropogenic activities (Bourtsoukidis et al, 2019;Bourtsoukidis et al, 2020;Pfannerstill et al, 2019;Wang et al, 2020). The three molecules presented in this study are the exception.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…This study focuses on the two crossings of the Arabian Sea during the AQABA campaign. The Arabian Sea was generally characterized by low values of VOCs, especially VOCs related to anthropogenic activities (Bourtsoukidis et al, 2019;Bourtsoukidis et al, 2020;Pfannerstill et al, 2019;Wang et al, 2020). The three molecules presented in this study are the exception.…”
Section: Resultsmentioning
confidence: 49%
“…2). Onboard the ship there were a weather station and four laboratory containers equipped with instrumentation for on-and offline measurement of a large suite of trace gases, particles, and radicals (Bourtsoukidis et al, 2019;Bourtsoukidis et al, 2020;Wang et al, 2020).…”
Section: Aqaba Campaignmentioning
confidence: 99%
“…Acetaldehyde (ethanal) is known to be an important contributor to the total ambient carbonyl concentration in the atmosphere. Various sources of acetaldehyde have been characterized previously, including direct emissions from vegetation and the ocean and secondary production from the OH-, NO3-, and O3-initiated photooxidation of hydrocarbons (Rottenberger et al, 2004;Wang et al, 2020b). Direct biogenic emissions may be of special importance for the Amazonian rainforest, as acetaldehyde and ethanol release have been reported to result from root anoxia (Bracho-Nunez et al, 2012;Holzinger et al, 2000;Rottenberger et al, 2008).…”
Section: Acetaldehydementioning
confidence: 99%
“…Global models have recently revealed discrepancies between simulated and measured acetaldehyde concentrations (Millet et al, 2010;Wang et al, 2019;Wang et al, 2020). Wang et al (2020) reported CH3CHO mixing ratios that were up to a factor of 10 higher than global chemistry-transport model (EMAC) results in the marine boundary layer around the Arabian Peninsula, implying missing sources in remote and polluted regions. Wang et al (2019) also found that models systematically underestimate CH3CHO compared to observations in the remote troposphere, implying a missing source of acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%